2014
DOI: 10.1080/14999013.2014.885471
|View full text |Cite
|
Sign up to set email alerts
|

Triple Stigma of Forensic Psychiatric Patients: Mental Illness, Race, and Criminal History

Abstract: Stigma involves negative beliefs and devaluations of people in socially identified groups, which some people internalize. Research has increasingly explored mental illness self-stigma, when people with mental illness believe society's negative beliefs are true of them (e.g., they are hopeless due to mental illness). Self-stigma predicts poorer functional and treatment outcomes. Forensic psychiatric patients experience multiple stigmas, yet no research has explored how stigmas due to mental illness, race, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 185 publications
(194 reference statements)
0
61
0
2
Order By: Relevance
“…The war's effects were significant in the United States; 1 in every 136 adults was incarcerated for drug possession in 2005 . Although public sentiment about criminalizing people for drug possession has waned, (eg, the U.S. Department of Justice has been prompting criminal deinstitutionalization and alternatives to incarceration through the “Second Chance Act”), research shows people who agree with criminal penalties for drug use still endorse the stigma of people labeled with SUD . Future research needs to unpack the relative impact of addiction and criminalization stigma as well as ways they interact.…”
Section: What Is Stigma?mentioning
confidence: 99%
“…The war's effects were significant in the United States; 1 in every 136 adults was incarcerated for drug possession in 2005 . Although public sentiment about criminalizing people for drug possession has waned, (eg, the U.S. Department of Justice has been prompting criminal deinstitutionalization and alternatives to incarceration through the “Second Chance Act”), research shows people who agree with criminal penalties for drug use still endorse the stigma of people labeled with SUD . Future research needs to unpack the relative impact of addiction and criminalization stigma as well as ways they interact.…”
Section: What Is Stigma?mentioning
confidence: 99%
“…(2) Unlike the stigma of mental illness, addiction stigma probably gains its most pernicious effects from being intertwined with criminality. For example, research shows people who endorse greater legal penalties for substance use agree more with greater discrimination against people with SUDs . Both these issues need to be incorporated into strategies meant to address addiction stigma.…”
Section: Introductionmentioning
confidence: 99%
“…The rights agenda may have less traction for people with addiction when the public is confronted with messages that legitimize this kind of stigma, especially in light of criminal activities. In Part I, research is discussed that showed people are more likely to withhold opportunities from substance users when they endorse criminal notions about addictions . The rights agenda has not until recently, been widely endorsed by substance use advocates.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although public sentiment about criminalising people for drug possession and use has waned (for example, the US Department of Justice has been prompting criminal deinstitutionalisation and alternatives to incarceration through the 'Second Chance Act'), research shows that people who agree with criminal penalties for drug use still endorse the stigma of people labelled with substance use disorder. 6 Addiction stigma also has an impact on interpretation of civil law. Consider, for example, reasonable adjustment requirements of the Equality Act in the UK or the Americans with Disabilities Act (ADA).…”
Section: Discrimination Against People With Addictions Is Legalmentioning
confidence: 99%